Functions and regulation of quorum-sensing in Agrobacterium tumefaciens - Faure, Denis; Lang, Julien (Frontiers in Plant Science, 2014)
In Agrobacterium tumefaciens, horizontal transfer and vegetative replication of oncogenic Ti plasmids involve a cell-to-cell communication process called quorum-sensing (QS). The determinants of the QS-system belong to the LuxR/LuxI class. The LuxI-like protein TraI synthesizes N-acyl-homoserine lactone molecules which act as diffusible QS-signals. Beyond a threshold concentration, these molecules bind and activate the LuxR-like transcriptional regulator TraR, thereby initiating the QS-regulatory pathway. For the last twenty years, A. tumefaciens has stood as a prominent model in the understanding of the LuxR/LuxI type of QS systems. A number of studies also unveiled features which are unique to A. tumefaciens QS, some of them being directly related to the phytopathogenic lifestyle of the bacteria. In this review we will present the current knowledge of QS in A. tumefaciens at both the genetic and molecular levels. We will also describe how interactions with plant host modulate the QS pathway of A. tumefaciens, and discuss what could be the advantages for the agrobacteria to use such a tightly regulated QS-system to disseminate the Ti plasmids.